A bioorthogonal chemical reporter for the detection and identification of protein lactylation. Issue 20 (6th May 2022) - Sun, Yanan; Chen, Yanchi; Peng, Tao
Abstract : YnLac is an alkynyl-functionalized l -lactate analogue that is metabolically incorporated into l -lactylated proteins in live cells, enabling the fluorescence detection and proteomic identification of novel l -lactylated proteins. Abstract : l -Lactylation is a recently discovered post-translational modification occurring on histone lysine residues to regulate gene expression. However, the substrate scope of lactylation, especially that in non-histone proteins, remains unknown, largely due to the limitations of current methods for analyzing lactylated proteins. Herein, we report an alkynyl-functionalized bioorthogonal chemical reporter, YnLac, for the detection and identification of protein lactylation in mammalian cells. Our in-gel fluorescence and chemical proteomic analyses show that YnLac is metabolically incorporated into lactylated proteins and directly labels known lactylated lysines of histones. We further apply YnLac to the proteome-wide profiling of lactylation, revealing many novel modification sites in non-histone proteins for the first time. Moreover, we demonstrate that lactylation of a newly identified substrate protein PARP1 regulates its ADP-ribosylation activity. Our study thus provides a powerful chemical tool for characterizing protein lactylation and greatly expands our understanding of substrate proteins and functions of this new modification.